2010 IEEE 71st Vehicular Technology Conference 2010
DOI: 10.1109/vetecs.2010.5494209
|View full text |Cite
|
Sign up to set email alerts
|

Safe Distance Based Location Privacy in Vehicular Networks

Abstract: To enhance driving safety in vehicle ad-hoc networks (VANETs), vehicles periodically broadcast safety messages with information of their precise positions to others. These broadcast messages, however, make it easy to track vehicles and will likely lead to violations of personal privacy. Unfortunately, most of the current location privacy enhancement methodologies in VANETs suffer some shortcomings and do not take driving safety into consideration. In this paper, we propose a safe distance based location privac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The fundamental concept of privacy preservation schemes in VANET is to periodically change the pseudonyms. There exists many schemes that have been proposed by researchers in which the concept of changing pseudonym is used to preserve the privacy of user [28][29][30][31][32][33][34][35][36]. Data owners often suppress their data for an untrusted trainer to train a classifier due to privacy concerns.…”
Section: Vanet Security Requirementsmentioning
confidence: 99%
“…The fundamental concept of privacy preservation schemes in VANET is to periodically change the pseudonyms. There exists many schemes that have been proposed by researchers in which the concept of changing pseudonym is used to preserve the privacy of user [28][29][30][31][32][33][34][35][36]. Data owners often suppress their data for an untrusted trainer to train a classifier due to privacy concerns.…”
Section: Vanet Security Requirementsmentioning
confidence: 99%
“…In order to assure the validity and privacy of an SRL and prevent privilege elevation attacks, an attachable blind signature is used by PPACP. Recently, Wu et al proposed a cryptanalysis of an attachable blind signature and demonstrate that the PAACP's Authorized Credential (AC) is not secure and private even if the AC is secretly stored in a tamper-proof device [10]. Their analysis showed that in PAACP, an eavesdropper can construct the AC from an intercepted blind document.…”
Section: Cryptanalysis Of a Paacpmentioning
confidence: 99%
“…Among various security threats, privacy preservation in VANETs is one of the new challenges of protecting users' private information. For instance, Chen and Wei [2,10] proposed a safe, distance-based location privacy scheme called SafeAnon. By simulating vehicular mobility in a cropped Manhattan map, they evaluated the performance of the SafeAnon scheme under various conditions to show that it could simultaneously achieve location privacy as well as traffic safety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among various security threats, privacy preservation in VANETs is one of the new challenges of protecting users' private information. For instance, Chen and Wei proposed a safe, distance-based location privacy scheme called SafeAnon [5,6]. By simulating vehicular mobility in a cropped Manhattan map, they evaluated the performance of the SafeAnon scheme under various conditions to show that it could simultaneously achieve location privacy, as well as traffic safety.…”
Section: Introductionmentioning
confidence: 99%